(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Over the past decade, there has been a significant increase in the number of patients with eating disorders, which is a very serious problem. This issue attracts great attention of scientists, since, according to the results of a ten-year observation of the follow-up data of patients, due to multiple somatic disorders, the patient’s life ends in death.